Facilitating Teaching Strategies and Active Learning in Greek Early Years Department Students - Eleni Tympa; Vasiliki Karavida; Vasiliki Filippa (Journal of Educational Issues, 2024)
The aim of the study was to examine whether participation of academic students in experiential activities during their semester lessons could facilitate their learning and improve their exam performance. The study involved 68 students of an Early Years Learning & Care Department, who volunteered and committed to attend all semester lessons. All students participated actively during the lessons. At the end of the semester students were interviewed with a semi-structured protocol on the experiences of the teaching process and on what they thought the impact of the process will be on written exams. Participants had been informed of the purposes of the study in advance, they had the right to withdraw at any time and anonymity was guaranteed. All students stated that they enjoyed the process, preferred it to a passive lecture, gained more knowledge and were more prepared for the exams. This interactive teaching process concerns both university teachers and students, requires planning and merits further discussion.